The Ellipse of Contemporary Reading or the Genre Nonsense - Miomir Petrović; Ivana Ercegovac (In Medias Res, 2014)
In the economic struggle, literary or rather, publishing overproduction has turned a book among other things, into commercial product, and the trend of frantic printing has spawned some new literary or “literary” genres. New literature, it can be said, has simplified the language, and to some point the literature itself. Thus, the emergence of the so-called “women writers” (chick lit-literature for chicks) in many ways devalued and degraded “women’s writing” - french feminist critique of society and the emergence of “airport novel” even more simplified the thriller that is easy reading by itself. The article problematizes the emergence of new genres as a way of playing up to the target groups, which also encourages the decadence of literature as art. It also discusses the issue of “lightness” of literature and attempts to answer whether any “easier” writer causes a “lighter” mind readers.